An Investigation of the Relationship Between Nursing Students’ Academic Writing Competence and Academic Literacy - Özalp, Cemal; Avşar, Gülçin (Ataturk Universitesi, 2026)
Objective: This study aimed to examine the relationship between academic writing competency and academic literacy levels among nursing students. Methods: Data were collected between January 15 and March 15, 2023. The study population consisted of 505 undergraduate, master’s, and doctoral nursing students enrolled at the Faculty of Nursing of a state Atatürk University. Data were gathered using a demographic information form, the Academic Writing Competency Scale, and the Academic Literacy Scale. Descriptive analyses and correlation tests were conducted with SPSS version 26.0. Results: Among the participants, 74.4% were aged 18–24 years, 66.6% were female, 92.5% had not received prior academic writing training, 55% had no formal English education, and 76.2% reported reading books once per month. The mean score for the Academic Writing Competency Scale was 3.24 (SD=0.786), while the mean score for the Academic Literacy Scale was 3.60 (SD=0.433). A moderate positive correlation was identified between academic writing competency and academic literacy (r=0.617, p<.001). Conclusion: The findings demonstrate a statistically significant moderate positive association between academic writing competency and academic literacy among nursing students. It is recommended that nursing curricula incorporate targeted interventions to enhance students’ academic writing and literacy skills, which are critical for evidence-based practice. © 2026, Ataturk Universitesi. All rights reserved.
Keywords: Academic Literacy; Academic Writing; Nursing Education; Nursing Students